The effect of a proposed training program with weights on the level of digital achievement in the shot put using the sliding method - عيسى مجد (Latakia University Journal -Medical Sciences Series, 2024)
The aim of the research is to identify the effect of training with weights on the level of achievement in shot put in a gliding way. The researcher used the experimental method, and the research sample consisted of (20) male students from the Faculty of Physical Education - Tishreen University in the third year, with an average of two groups, an experimental group (10) Students and a control group (10) students, giving them three attempts for each of them and analyzing the results of the best attempt. The training program was designed, which lasted for (8) weeks, and consisted of (16) educational units at a rate of two units per week, after which the tribal tests were implemented. Then the training program was applied, after that, the post-tests were conducted in the same way as the pre-tests. Then the data was analyzed using the arithmetic mean, standard deviation, skewness coefficient, Pearson simple correlation coefficient, and T-Test. The results of the study concluded that the training program used led to an improvement in the level of achievement in shot put in a gliding way The researcher recommended the use of training with weights in developing the level of achievement in shot put, and conducting similar studies for various athletics activities.